عصرحاضرمیں مسئلہ تسعیر کا فقہی جائزہ: LEGAL ASSESSMENT OF THE ISSUE OF FIXING PRICE IN CONTEMPORARY PERIOD (Zia e Tahqeeq, 2025)
This paper aims to analyze the legal status of fixing the prices (tasir) of regular commodities by government. One of the biggest problems facing developing countries is the issue of the high prices of regular things. The owners of things take advantage of the needs of the peopleand demand the high prices. Therefore, the traders, sellers and businessmen exploit the consumers because of the free marketing economical system which focuses on rule of demand and supply for the determination of price. On the other hand, it is the duty of government to ensure the welfare of the community. Thus, the government sets prices of commodities and it bounds the sellers to sell the things on fixed prices. However, there is legal debate around thepermissibility of fixing the prices of commodities in Islamic law. In this article this case will be examined that whether the fixing the prince or price control is an Islamic solution or not.